Association between dietary intake of vitamin D and risk of depression, anxiety, and sleep disorders among physically active adults: a cross-sectional study - Arabshahi, Vajiheh; Khoddami, Mehrad; Milajerdi, Maryam; Moabedi, Mahdi; Milajerdi, Alireza (Frontiers in Nutrition, 2024)
Introduction: Rare studies have been done to investigate the association between dietary intakes of vitamin D and the risk of mental health disorders among athletes. The current study aimed to investigate the association between this vitamin intake and the risk of depression, anxiety, and sleep disorders among a group of Iranian physically active adults. Methods: This cross-sectional study was conducted among 690 healthy athletes (18-50 years, mean BMI between 20 and 30) in Kashan, Iran. The usual dietary intake of participants was assessed by a 147-item FFQ. Depression was assessed by the Beck Depression Inventory-II (21item), anxiety by the Beck Anxiety Inventory (21-item), and sleep disorders by the Pittsburgh Sleep Quality Index questionnaires. Statistical analyses were done by using SPSS version 18. P values <0.05 were considered significant.Results: No significant association was found between vitamin D dietary intake and risk of depression in the full-adjusted model (OR: 0.96, 95% CI: 0.62, 1.51). In contrast, participants at the highest tertile of vitamin D consumption had a 49% lower risk of anxiety than those at the lowest tertile (OR: 0.51, 95%: 0.29, 0.87). Moreover, a significant 46% lower risk of sleep disorders was found among those with the highest intake of vitamin D in comparison to participants with the lowest intake (OR: 0.54, 95% CI: 0.37, 0.78).We found a significant association between dietary vitamin D intake and reduced risk of anxiety and sleep disorders, but not with depression, in this study. Further prospective studies are recommended for future investigations.